Case Report: Alpha-fetoprotein-producing urothelial carcinoma of the bladder - Huang, Haibing; Ding, Youping; Fang, Yuju; Xie, Kunlin; Zhong, Chengyong; Fan, Haiye; Zou, Xiaofeng; Xie, Tianpeng (Frontiers in Oncology, 2025)
Elevated serum levels of alpha-fetoprotein (AFP) are commonly associated with hepatocellular carcinoma or germ cell tumors. AFP-producing urothelial carcinoma of the bladder is very rare. We report a case of bladder urothelial carcinoma with significantly elevated AFP levels. A 60-year-old man was admitted for gross hematuria. Computed tomography urography revealed multiple large tumors of the bladder. The serum level of AFP was up to 2,329 ng/ml. No hepatic tumors or testicular tumors were detected. Although the hepatitis B surface antigen test was positive, the liver function test was normal. The patient underwent robotic-assisted laparoscopic radical cystectomy with ileal conduit urinary diversion. Postoperative pathology revealed high-grade muscle invasive bladder urothelial carcinoma and immunohistochemical staining of the tumor cells showed strong AFP positivity. After surgery, the patient’s serum AFP levels dropped sharply and decreased to normal 4 weeks after the operation. In conclusion, AFP-producing bladder urothelial carcinoma is rare, and the mechanism and pathophysiology remain unclear and require further investigation.